A Cryophyte Transcription Factor, CbABF1, Confers Freezing, and Drought Tolerance in Tobacco - Yue, Xiule; Zhang, Guoyan; Zhao, Zhen; Yue, Jinli; Pu, Xiaohong; Sui, Mengjun; Zhan, Yi; Shi, Yulan; Wang, Zhenyu; Meng, Guanghua; Zhao, Zhixing; An, Lizhe (Frontiers in Plant Science, 2019)
Abscisic acid responsive element binding factors (ABFs) play crucial roles in plant responses to abiotic stress. However, little is known about the roles of ABFs in alpine subnival plants, which can survive under extreme environmental conditions. Here, we cloned and characterized an ABF1 homolog, CbABF1, from the alpine subnival plant Chorispora bungeana. Expression of CbABF1 was induced by cold, drought, and abscisic acid. Subcellular localization analysis revealed that CbABF1 was located in the nucleus. Further, CbABF1 had transactivation activity, which was dependent on the N-terminal region containing 89 residues. A Snf1-related protein kinase, CbSnRK2.6, interacted with CbABF1 in yeast two-hybrid analysis and bimolecular fluorescence complementation assays. Transient expression assay revealed that CbSnRK2.6 enhanced the transactivation of CbABF1 on ABRE cis-element. We further found that heterologous expression of CbABF1 in tobacco improved plant tolerance to freezing and drought stress, in which the survival rates of the transgenic plants increased around 40% and 60% respectively compared with wild-type plants. Moreover, the transgenic plants accumulated less reactive oxygen species, accompanied by high activities of antioxidant enzymes and elevated expression of stress-responsive genes. Our results thus suggest that CbABF1 is a transcription factor that plays an important role in cold and drought tolerance and is a candidate gene in molecular breeding of stress-tolerant crops.